Continuity correction of Pearson’s chi-square test in 2x2 Contingency Tables: A mini-review on recent development (Epidemiology, Biostatistics, and Public Health, 2022)
The Pearson’s chi-square test represents a nonparametric test more used in Biomedicine and Social Sciences, but it introduces an error for 2x2 contingency tables, when a discrete probability distribution is approximated with a continuous distribution. The first author to introduce the continuity correction of Pearson’s chi-square test has been Yates F. (1934). Unfortunately, Yates’s correction may tend to overcorrect of p-value, this can implicate an overly conservative result. Therefore many authors have introduced variants Pearson’s chi-square statistic, as alternative continuity correction to Yates’s correction. The goal of this paper is to describe the most recent continuity corrections, proposed for Pearson’s chi-square test.
Keywords: Pearson’s x2 statistic; continuity correction; 2x2 contingency table; Yates’s continuity correction; Serra’s continuity correction